The Principle of Good Faith in The Preliminary Agreement (Voor Overeenkomst) in The House Sale and Purchase Agreement (Semarang State Court Study No 467/Pdt.G/2022/SMG) - Nugroho Adi Wicaksono; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2023)
This research aims to analyze the principle of good faith related to preliminary agreements (voor overeenkomst) in the context of house sale and purchase agreements. This research takes a case study from the Semarang District Court decision with case number 467/Pdt.G/2022/SMG. The research method used is normative legal research with a statutory approach and a case approach. The data used in this research consists of primary and secondary legal materials, including related laws and regulations, court decisions, as well as relevant legal literature. The research results show that the principle of good faith has an important role in the preliminary agreement (voor overeenkomst) in the house sale and purchase agreement. The principle of good faith involves integrity and honesty between the parties involved in the agreement. The Semarang District Court's decision in this case shows the need to apply the principle of good faith in deciding disputes that arise related to preliminary agreements.